Development of Flashcard Media in Improving Cultural Knowledge of Early Childhood Students - Everhard Markiano Solissa; Rahayu Setyaningsih; Heppy Sapulete; Sumarni Rumfot; Agus Rofi’i (Journal of Childhood Development, 2023)
The purpose of this study is to develop flashcard media for introducing the culture of Central Java. This study also used development research (R&D), which was carried out in two trials, namely the one-to-one trial and the small group trial. The subjects in this study were to get to know the culture of the Central Java region, while the objects in this study were 10 students. The data were collected using guidelines in the form of observation, interviews, questionnaires and documentation. The analysis used is qualitative and quantitative data analysis. The results of this study indicate that the Flashcard media developed through a series of trials and validations is declared feasible. The results of the one-to-one trial get a percentage of 87.50%, and the results of the small group trial get a percentage of 83.60%; both categories are very good or very decent. Therefore, based on the results of this study, it can be concluded that Flashcard media is appropriate for use in learning to introduce Central Java regional culture to students.